What is driving the global decline of human fertility? Need for a multidisciplinary approach to the underlying mechanisms - Aitken, Robert John (Frontiers in Reproductive Health, 2024)
An intense period of human population expansion over the past 250 years is about to cease. Total fertility rates are falling dramatically all over the world such that highly industrialized nations, including China and the tiger economies of SE Asia, will see their populations decline significantly in the coming decades. The socioeconomic, geopolitical and environmental ramifications of this change are considerable and invite a multidisciplinary consideration of the underlying mechanisms. In the short-term, socioeconomic factors, particularly urbanization and delayed childbearing are powerful drivers of reduced fertility. In parallel, lifestyle factors such as obesity and the presence of numerous reproductive toxicants in the environment, including air-borne pollutants, nanoplastics and electromagnetic radiation, are seriously compromising reproductive health. In the longer term, it is hypothesized that the reduction in family size that accompanies the demographic transition will decrease selection pressure on high fertility genes leading to a progressive loss of human fecundity. Paradoxically, the uptake of assisted reproductive technologies at scale, may also contribute to such fecundity loss by encouraging the retention of poor fertility genotypes within the population. Since the decline in fertility rate that accompanies the demographic transition appears to be ubiquitous, the public health implications for our species are potentially devastating.